Urgency and Mechanism of Biosynthesis of Marine Microbial Secondary Metabolites - Albetina Sedaca (International Journal of Science and Society, 2020)
Marine microorganism is one of biologically active potential resources of secondary metabolites. Its potency are so promising that the knowledge of how its secondary metabolite occured need to be studied and collected. Those knowledges will enable further study is improving secondary metabolite production in the laboratory. In nature, secondary metabolites synthesis occur when there are effect of both biotic and abiotic factors such as sea water and microbe symbiosis with other living materials. When this is explained in metabolic pathways, secondary metabolite synthesis affected by available nutrient and regulated by autoinducer molecules through quorum sensing mechanism.